Management of hyponatraemia in patients with acute cerebral insults. Issue 3 (1st September 2001) - Albanese, A; Hindmarsh, P; Stanhope, R
Abstract : Hyponatraemia is a common finding in patients with acute cerebral insults. The main differential diagnosis is between syndrome of inappropriate ADH secretion and cerebral salt wasting. Our aim is to review the topic of hyponatraemia in patients with acute cerebral insults and suggest a clinical approach to diagnosis and management.